Reliability of rehabilitative ultrasonographic imaging for muscle thickness measurement of the rhomboid major. (17th November 2014) - Jeong, Ju Ri; Ko, Young Jun; Ha, Hyun Geun; Lee, Wan Hee
Summary: Objective: This study was to establish inter‐rater and intrarater reliability of the rehabilitative ultrasonographic imaging (RUSI) technique for muscle thickness measurement of the rhomboid major at rest and with the shoulder abducted to 90°. Participants: Twenty‐four young adults (eight men, 16 women; right‐handed; mean age [±SD], 24·4 years [±2·6]) with no history of neck, shoulder, or arm pain were recruited. Methods: Rhomboid major muscle images were obtained in the resting position and with shoulder in 90° abduction using an ultrasonography system with a 7·5‐MHz linear transducer. In these two positions, the examiners found the site at which the transducer could be placed. Two examiners obtained the images of all participants in three test sessions at random. Intraclass correlation coefficients (ICC) were used to estimate reliability. Results: All ICCs (95% CI) were >0·75, ranging from 0·93 to 0·98, which indicates good reliability. The ICCs for inter‐rater reliability ranged from 0·75 to 0·94. For the absolute value of the difference in the intra‐examiner reliability between the right and left ratios, the ICCs ranged from 0·58 to 0·91. Conclusion: In this study, the intra‐ and interexaminer reliability of muscle thickness measurements of the rhomboid major were good. Therefore, we suggest that muscle thickness measurements of the rhomboid major obtained with the RUSI technique would be useful for clinical rehabilitative assessment.